Mengembangkan SMK Muhya Gemilang Sebagai Sekolah Berkarakter Dengan Menjadikannya Sebagai Katup Pengaman Ekonomi Rakyat - Wakhudin, Wakhudin; Purbomartono, Cahyono; Wijarnako, Raden Beny (Civiliza Publishing, 2024)
The background to this service activity is Indonesia's increasingly difficult economic conditions amidst rising dollar prices, inflation, and increasing unemployment and poverty rates. The main aim of this activity is to develop Muhya Gemilang Vocational School as a school with character that can act as a safety valve for the people's economy by managing local potential and the creative economy. The method of implementing activities involves an agreement between the service and the Kroya Muhammadiyah (PCM) Branch Leadership, as well as collaboration with Muhya Gemilang Vocational School. This activity includes fostering the discipline of educators and education personnel, building school infrastructure, and utilizing waqf land for agriculture and fisheries. Socialization and training are provided to students regarding fish farming, vegetable growing, and other entrepreneurial skills such as cutting hair, opening a motorbike repair shop, and becoming a content creator. The findings from this activity show that two main programs are being built by Muhya Gemilang Vocational School, namely building community trust and building the school as a center of excellence. Increasing the discipline of educators and education personnel has succeeded in increasing the number of students registering. Apart from that, collaboration with the Muhammadiyah University of Purwokerto in fish cultivation provides students with practical skills to manage the surrounding environment to be more productive. In conclusion, this activity succeeded in increasing public trust in Muhya Gemilang Vocational School and providing entrepreneurial skills to students who can contribute to overcoming local economic problems. A new and important aspect of this activity is the bottom-up approach in developing the creative economy through school initiatives and collaboration with the community.